Juridical Analysis of the Annulment of the Execution of Arbitral Awards by the District Court in the Supreme Court Decision - Labi, Moses Sampe Karaeng Arung (Rechtsvinding, 2025)
Arbitral awards in Indonesia are final and binding under Article 60 of Law No. 30/1999, yet District Courts (DCs) frequently annul enforcement through Article 70, creating legal uncertainty. This article examines annulment patterns in the Jakarta, Bekasi, and Tangerang DCs, alongside the Supreme Court’s (SC) role in safeguarding arbitral finality. Employing a doctrinal legal method through case analysis of four SC rulings (2021–2024) and comparative review of DC reasoning, the study identifies three dominant grounds: Jakarta DC broadly invoked public policy violations (60% of cases), Bekasi DC emphasized procedural defects (75%), while Tangerang DC referred to public interest conflicts. However, the SC overturned 85% of these rulings, reaffirming that (1) Article 70 applies only to concrete procedural or public policy breaches, (2) DCs lack authority to reassess the merits of arbitral awards, and (3) non-material defects cannot justify annulment. These findings reveal inconsistent DC interpretations, particularly the expansive notion of public policy adopted by Jakarta DC, which contrasts with the SC’s narrow, procedure-focused approach. Such disparities undermine arbitral finality and discourage foreign investment. The SC thus plays a pivotal role as a legal filter, though systemic reforms remain necessary through specialized judicial training, jurisprudential harmonization, and legislative revision of Indonesia’s Arbitration Law.